2019
DOI: 10.18052/www.scipress.com/ijppe.14.16
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological Documentation of Medicinal Plants Used in the Traditional Treatment of Hypertension in Tarfaya Province, Morocco

Abstract: The use of plants to treat chronic diseases is part of an ancient Moroccan tradition. This study will present the first relevant documentation on medicinal plants used in the treatment of hypertension in Tarfaya province. This study aimed to collect and document information on medicinal plants traditionally used by the local population of Tarfaya province for the treatment of hypertension. Ethnobotanical surveys were conducted using 150 questionnaires in the study area. Documented data were evaluated using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 205 publications
(89 reference statements)
1
5
0
Order By: Relevance
“…This result can be explained by the attachment of women to the traditional component as well as by the ease of transmission of this information between them, and they are concerned with the treatment of themselves and their families. These results are in agreement with those reported in other regions of Morocco (El alami et al 2017, Idm'hand et al 2019, Ziyyat et al 1997. (Table 1) On marital status, 65.05% were married, 17.23% were single, 11.65% were widowed and 6.06% were divorced, These results can be explained by the fact that married people take care of their health and that of their children, especially in rural areas, in order to minimize the material expenses of the doctor and the pharmacist, the difference between families status was statistically significant (P = 0.000).…”
Section: Resultssupporting
confidence: 93%
“…This result can be explained by the attachment of women to the traditional component as well as by the ease of transmission of this information between them, and they are concerned with the treatment of themselves and their families. These results are in agreement with those reported in other regions of Morocco (El alami et al 2017, Idm'hand et al 2019, Ziyyat et al 1997. (Table 1) On marital status, 65.05% were married, 17.23% were single, 11.65% were widowed and 6.06% were divorced, These results can be explained by the fact that married people take care of their health and that of their children, especially in rural areas, in order to minimize the material expenses of the doctor and the pharmacist, the difference between families status was statistically significant (P = 0.000).…”
Section: Resultssupporting
confidence: 93%
“…In this province, the most frequently used plants include Allium sativum, Allium cepa, Olea europaea, Searsia tripartita, Ammodaucus leucotrichus and Myrtus communis. The survey revealed that leaves were the most frequently used part in herbal preparations (Idm'hand et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…These were: Nerium oleander, Citrullus colocynthis, Ferula assa-foetida, Papaver somniferum, Mandragora officinalis, Tetraena gaetula, Ricinus communis, Peganum harmala and Datura stramonium (Eddouks et al, 2002). (Eddouks et al, 2002;Idm'hand et al, 2019;Jouad et al, 2001;Tahraoui et al, 2007;Ziyyat et al, 1997 Eddouks et al, 2002;Idm'hand et al, 2019;Jouad et al, 2001;Tahraoui et al, 2007;Ziyyat et al, 1997 Eddouks et al, 2002;Idm'hand et al, 2019;Tahraoui et al, 2007;Ziyyat et al, 1997) Tamarix aphylla (L.) H.Karst.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations